Training and confidence in undertaking child protection work as reported by New Zealand paediatricians. (29th May 2019) - Neels, Aimee; Tuohy, Pat; Elder, Dawn
Abstract : Aim: In New Zealand and rural Australia, general paediatricians undertake the majority of child protection (CP) medical assessments. This study aimed to document what New Zealand paediatricians think about their role in CP and their perceived preparedness for this work. Methods: A 43‐item SurveyMonkey questionnaire was sent to paediatricians working in CP. Questions explored demographic detail, CP work undertaken clinically and with regard to teaching and paediatrician confidence and experience in areas of CP. A separate questionnaire documented organisational CP work. Results: A total of 79 paediatricians, 45 (57%) female, responded from 15 of 20 District Health Boards. For 73%, CP was less than 10% of their weekly workload, with 42% indicating they had been the lead paediatrician for fewer than five cases in the preceding 12 months. Paediatricians were more confident managing physical abuse than sexual abuse cases with regard to initial assessments, report writing and appearances in court. Just over a third reported at least once feeling personally threatened or unsafe while involved in a CP case. Only 29% were satisfied with their level of training, and 73% agreed they would like more CP training. Conclusions: Paediatricians undertake a number of roles in CP but do not feel confident in all these roles. More attention needs to be given to training in CP in general paediatric physician training in New Zealand.